Activity of cefepime/zidebactam (WCK 5222) against 'problem' antibiotic-resistant Gram-negative bacteria sent to a national reference laboratory. (24th March 2021) - Mushtaq, Shazad; Garello, Paolo; Vickers, Anna; Woodford, Neil; Livermore, David M
Abstract: Background: Triple-action diazabicyclooctanes, e.g. zidebactam, combine β-lactamase inhibition, antibacterial activity, and 'enhancement' of PBP3-targeted β-lactams. Objectives: To examine the activity of cefepime/zidebactam against consecutive 'problem' Gram-negative bacteria referred to the UK national reference laboratory. Methods: MICs were determined by BSAC agar dilution for 1632 Enterobacterales, 745 Pseudomonas aeruginosa and 450 other non-fermenters, categorized by carbapenemase detection and interpretive reading. Results: Universal susceptibility to cefepime/zidebactam 8 + 8 mg/L was seen for otherwise multidrug-resistant Enterobacterales with AmpC, extended-spectrum, K1, KPC and OXA-48-like β-lactamases, or with impermeability and 'unassigned' mechanisms. Unlike ceftazidime/avibactam and all other comparators, cefepime/zidebactam 8 + 8 mg/L also inhibited most (190/210, 90.5%) Enterobacterales with MBLs. Resistance in the remaining minority of MBL producers, and in 13/24 with both NDM MBLs and OXA-48-like enzymes, was associated with Klebsiella pneumoniae ST14. For Pseudomonas aeruginosa, MICs of cefepime/zidebactam rose with efflux grade, but exceeded 8 + 8 mg/L for only 11/85 isolates even in the highly-raised efflux group. Among 103 P. aeruginosa with ESBLs or MBLs, 97 (94.5%) were inhibited by cefepime/zidebactam 8 + 8 mg/L whereas fewer than 15% were susceptible to any comparator. MICs for Acinetobacter baumannii with acquired OXA carbapenemases clustered around 8 + 8 to 32 + 32 mg/L, with higher values for MBL producers. A strong enhancer effect augmented activity against many isolates that were highly resistant to cefepime and zidebactam alone and which had mechanisms not inhibited by zidebactam. Conclusions: Assuming successful clinical trials, cefepime/zidebactam has scope to widely overcome critical resistances in both Enterobacterales and non-fermenters.